Knee biomechanics of the support leg in soccer kicks from three angles of approach - Kellis, E.; Katis, A.; Gissis, I. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: To examine knee joint kinematics, electromyographic (EMG) activity patterns and ground reaction forces (GRF) during an instep soccer kick from three different approaches relative to the ball. METHODS: Ten male soccer players performed maximum kicks from 0 rad (K0), 0.81 rad (K45), and 1.62 rad (K90) angle between the players' starting position and the position of the ball. GRF data and 3-D kinematics and EMG activity of the vastus medialis (VM), vastus lateralis (VL), and biceps femoris (BF) muscles of the lower leg were recorded. RESULTS: colon; Compared with K0, K90, and K45 demonstrated higher medial and posterior GRF and lower anterior GRF. K90 and K45 also demonstrated higher external rotation displacement, maximum flexion, internal rotation, abduction, and adduction velocity of the tibia relative to the femur of the support leg compared with K0 (P < 0.01). The BF EMG before and immediately after ground contact was also higher in K90 and K45 compared with K0 (P < 0.01). CONCLUSION: Soccer kicks using a high angle of approach increase the medial and posterior GRF, which is indicative of an altered stance during the kick, resulting in an altered balance. Such kicks are accompanied by significant alterations in knee joint kinematics and an increased BF activation around ground contact. Soccer kicks from an angled approach may induce significant loads to knee joint structures of the support leg.